From “Water Liars” to Yonder Stands Your Orphan: Pastimes, Sports, and Games Inside/Outside the Frame of Barry Hannah’s Eagle Lake Stories - Vice, Brad (American & British Studies Annual, 2025)
For most of his career, Mississippi author Barry Hannah was deemed the postmodern heir to William Faulkner and is best known for the short fiction in his landmark collection Airships (1978), which begins with the muchanthologized story “Water Liars.” Like many of the meta-fictionalist masters of the 1970s (Barth, Coover, etc.), Hannah stepped inside/outside the frame of his fictions, often in his case by using highly elevated language, and syntax to depict a rogue’s gallery of down-and-out characters, as well as the construction of numerous autobiographical personas, which wink and wave to his initiated readers. Thus, Hannah’s fiction is not only funny, it is playful, as if to invite the reader into some fictional game. As Hannah’s career developed, this sense of gamesmanship only seemed to increase as the characters and settings of many fictions began to reappear or return for cameo appearances. The characters first introduced in “Water Liars” reappear intermittently throughout Hannah’s thirty-year career and populate the community we come to know as Eagle Lake, the setting for Hannah’s final novel Yonder Stands Your Orphan (2001). While other critics have examined Hannah’s passions for tennis and golf as having thematic significance, this article will focus on the pastime of fishing as well as many other intertextual games played inside/outside the frame of Hannah’s Eagle Lake Stories, to reckon with how they inform his swan song, Yonder Stands Your Orphan. Ultimately, the paper will consider to what extent writing itself is a literary game on a meta level, a dynamic in which writers and tellers of tall tales strive against not only their peers but also their forbears.